International comparison of drug prices with Malaysia : a systematic review - Amirul A; Ong, Siew Chin (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
High drug price is a hot topic in Malaysia. In this systematic review of drug price comparison studies, we report on international comparison of drug prices with Malaysia. We systematically searched PubMed, Cochrane Library, ScienceDirect and Scopus for peer-reviewed articles. Only studies that made comparison internationally were included. Cost-effectiveness studies, budget impact analysis or costing studies were excluded. A total of 10 studies were included. Nine studies compared the price with median international reference prices (IRPs). Only one study compared the price with another country. The drug price in Malaysia forboth government and public sectors was higher than IRP. This review provides the information that the drug price in Malaysia is higher than the international standard. The number of published studies in the drug pricing area is still inadequate with only one study that compares Malaysia drug price with another country. More studies are needed to improve Malaysia’s drug pricing system.